Pengaruh Tingkat Pemahaman Dan Kesiapan Pelaku Umkm Terhadap Implementasi Sak Emkm Pada Umkm Di Kecamatan Telanaipura Kota Jambi - Nadia Ladita; Putri Apria Ningsih; Nurfitri Martaliah M E K (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Financial reports have the aim of providing information on the financial position, financial performance and cash flow reports of an entity that is useful for a large number of users in making economic decisions by anyone who is not in a position to request special financial reports to meet these information needs. Research with the title